Solvothermal Synthesis of Monodisperse Porous Zirconia Spheres with Large Surface Area. Issue 47 (5th November 2020) - Kan, Kai; Yamamoto, Emi; Ohtani, Masataka; Kobiro, Kazuya
Abstract : We developed non‐aggregated monodisperse ZrO2 porous spheres by a one‐pot single‐step solvothermal synthesis. A mixture of zirconium(IV) tetra‐ n ‐butoxide as a metal source and acetylacetone as an additive in ethanol was heated up to 300 °C in a 10 mL batch type reactor to yield perfectly monodisperse porous spheres of ZrO2 in almost quantitative yield with large surface area of 301 m 2 /g as well as nano‐concave‐convex surface structure. Especially, the concentration of acetylacetone was crucial in the reaction to form beautiful spheres. The reaction was easily scaled‐up to 500 mL autoclave scale yielding porous spheres with 244 m 2 /g specific surface area. The monodisperse ZrO2 porous spheres worked as an effective catalyst support comprising Ni nanoparticles, exhibiting in excellent dispersibility of the Ni nanoparticles. The resultant monodisperse ZrO2 porous spheres were tested as a catalyst for highly exothermic CO2 methanation, resulting in superior catalytic activity and thermal tolerance during repeated heating‐cooling cycles of three‐run tests. Abstract : Monodisperse ZrO2 porous spheres with large surface area by one‐pot single‐step solvothermal reaction. The monodisperse ZrO2 porous spheres worked as an effective catalyst support for Ni nanoparticles with excellent dispersibility. Thus, the ZrO2 porous‐sphere‐supported Ni catalyst exhibited superior activity for CO2 methanation and better low temperature activity.